2016
DOI: 10.3329/bjog.v28i2.30092
|View full text |Cite
|
Sign up to set email alerts
|

Role of High Dose Calcium in the Prevention of Preeclampsia

Abstract: Objectives: To assess the effect of supplementation of high dose of calcium(2gm) in prevention of preeclampsia.Materials & Methods: A randomized controlled clinical trial on 272 healthy nulliparous woman were randomly allocated into two groups by means of a computer generation randomization list. From 20 weeks of gestation until delivery who received 2gm of oral elemental calcium per day (n=127 )were assigned to high dose calcium group or the study group and 145 women were assigned to low dose calcium or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Of the 720 records identified, 30 RCTs (20 445 women) were eligible for the calcium supplementation versus placebo/no therapy meta‐analysis 16–45 ; and one additional RCT (272 women) was eligible for the high‐ versus low‐dose calcium NMA (Figure S1). 46 Reasons for exclusion are detailed in Table S2, and included seven continuing trials 47–53…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 720 records identified, 30 RCTs (20 445 women) were eligible for the calcium supplementation versus placebo/no therapy meta‐analysis 16–45 ; and one additional RCT (272 women) was eligible for the high‐ versus low‐dose calcium NMA (Figure S1). 46 Reasons for exclusion are detailed in Table S2, and included seven continuing trials 47–53…”
Section: Resultsmentioning
confidence: 99%
“…The NMA (25 trials, 15 038 women) included 24 trials in the meta‐analysis (details presented in Table 1), plus a trial of 2000 mg/day versus 500 mg/day elemental calcium from 20 weeks of gestation, in healthy nulliparous women (at low risk), with low baseline calcium intake in India 46 . Trials of high‐dose and low‐dose calcium, with roughly similar frequency, enrolled women at high risk (trials 18,22,27,31,32,34,38,39,43 with high dose; trials 16–18,23–26,36 with low dose) or women at low risk (trials 19,21,28–30,35,42,44–46 with high dose; trials 20,33,37,41and46 with low dose) of pre‐eclampsia, women with a low average baseline dietary intake of calcium (trials 18,19,22,28,30–32,34,35,39,40,44–46 with high dose; trials 16–18,20,23–26,33,36,37,41,46 with low dose) and women who initiated calcium supplementation early (trials 28,29,44 with high dose; trials 16,25,37 with low dose) or late (trials 18,19,21,22,27,30–32,34,35,38–40,42–46 with high dose; trials 17,18,20,23,24,26,33,36,41,46 with low dose) in pregnancy. The six trials among populations with adequate average calcium intake (trials 21,27,29,38,42,43 ) were not included in the NMA because they were all were high‐dose calcium trials and their inclusion would have violated the assumption of transitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included 48 studies, only 17 studies ( 14 , 16 , 17 , 48 – 51 , 53 , 54 , 56 58 , 60 , 62 , 64 – 66 ) reported the specific random grouping. In addition, only 12 studies ( 14 , 48 – 50 , 53 , 54 , 56 58 , 62 , 65 , 66 ) described the detailed methodology for hiding the random distribution sequences, leading to high risk of selection bias.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, implementation and measurement bias was at high risk. Furthermore, a risk of loss of follow-up bias was seen as there was a loss of follow-up in nine studies ( 14 , 15 , 17 , 49 , 52 , 56 , 60 , 62 , 64 ). Only nine studies ( 14 16 , 48 , 50 , 62 , 64 – 66 ) reported research protocols, leading to a high-risk of reporting bias ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%